Study of Dynamic Sorption in Adsorption Refrigeration Cycle (Journal of Engineering, 2014)
This paper shows the characteristics of temperature and adsorbed (water vapor) mass rate distribution in the adsorber unit which is the key part to any adsorption refrigeration system. The temperature profiles of adsorption/desorption phases (Dynamic Sorption) are measured experimentally under the operating conditions of 90oC hot water temperature, 30oC cooling water temperature, 35oC adsorption temperature and cycle time of 40 min. Based on the temperature profiles, The mass transfer equations for the annulus adsorbent bed are solved to obtain the distribution of adsorption velocity and adsorbate concentration using non-equilibriummodel. The relation between the adsorption velocity with time is investigated during the process of adsorption. The practical cycles of adsorption and desorption were stated dependent on the variables obtained from the experiment and equations calculations.The results show that the adsorption velocity is diminished after a period of 20 min. The maximum value of the adsorbed water vapor concentration on silica gel is 0.12 kg water/kg adsorbent (adsorption phase) and the minimum value of the water content into silica gel is 0.04 kg water/kg adsorbent (desorption phase) producing a dynamic sorption of kg water/kg adsorbent.